2022
DOI: 10.32604/iasc.2022.023763
|View full text |Cite
|
Sign up to set email alerts
|

Federated Learning for Privacy-Preserved Medical Internet of Things

Abstract: Healthcare is one of the notable areas where the integration of the Internet of Things (IoT) is highly adopted, also known as the Medical IoT (MIoT). So far, MIoT is revolutionizing healthcare because it provides many advantages for the benefit of patients and healthcare personnel. The use of MIoT is becoming a booming trend, generating a large amount of IoT data, which requires proper analysis to infer meaningful information. This has led to the rise of deploying artificial intelligence (AI) technologies, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…N.N. Thilakarathne et al [ 39 ] suggested a general strategy for federated learning (FL) as a potential solution to learning about Medical IoT (MIoT) that does not necessitate moving private and sensitive data to a central cloud. In [ 40 ], a predictive approach utilizing the cloud and an IoT-based database is suggested for forecasting the diseases that used the patients’ data collected from biosensors.…”
Section: Related Workmentioning
confidence: 99%
“…N.N. Thilakarathne et al [ 39 ] suggested a general strategy for federated learning (FL) as a potential solution to learning about Medical IoT (MIoT) that does not necessitate moving private and sensitive data to a central cloud. In [ 40 ], a predictive approach utilizing the cloud and an IoT-based database is suggested for forecasting the diseases that used the patients’ data collected from biosensors.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, with the further development of 5G IoT technology, privacy and security have become critical points for the industry to consider [1]. FL [2] dramatically guarantees data privacy in the model training process [3] and provides an effective solution to the islanding effect in ML. Based on securing the data privacy of industrial devices, FL can incorporate numerous industrial devices into the ML training process, saving communication resources during model training [4] and improving the training convergence rate and learning accuracy [5].…”
Section: Introductionmentioning
confidence: 99%